Knowledge Management and Tourism - Knowledge Transfer in the Hospitality Industry: From A Germany Perspective - Braun, Christine (2008)
The use of knowledge management has gained increased interest from academics and practitioners, however there is still a lack of empirical research in tourism and is particularly underdeveloped in the hospitality industry. Knowledge Management (KM) encompasses at least three components: knowledge creation, knowledge transfer and knowledge utilisation. This study investigates how knowledge management strategies, in particular knowledge transfer, are being utilised in the German hotel industry. The main purpose is to elaborate the content and context of knowledge transfer, the techniques, and who the knowledge workers are. To achieve this, 22 semi-structured interviews were administered in five upmarket hotels (between 50 and 100 employees) in Bavaria, South Germany. The sample included personnel from senior management and assistant positions and one hotel owner. The study provides some interesting insights into the roles of knowledge workers, the content of operational knowledge transferred, the organisational context, and techniques of knowledge transfer and storing. The findings show that KM practices are in place, even if this has been done unintentionally. Employees perceive themselves in the role of a knowledge worker; however this is dependent on the team level and the role of provider or receiver. Further research is needed to investigate the phenomenon in a greater depth and breadth, and advance empirical research to the contribution of KM in tourism.